The Myanmar Military Coup in 2021 and the Future of Democracy - Siti Ghina Fauziah; Made Fitri Maya Padmi (Budapest International Research and Critics University, 2022)
The coup that was again carried out by the Myanmar military junta brought Myanmar a flashback from the coup that had previously occurred. The democracy that the Burmese people hope for is always hampered due to the coups that keep happening again. This study aims to analyze the future of Myanmar's democracy. The research method used in this paper is a descriptive qualitative method using data collection through documents which will then be drawn from all the data obtained.